Pengaruh Penerapan Model Experiential Learning Terhadap Tingkat Pengetahuan Konseptual dan Faktual pada Pembelajaran IPA Peserta Didik Kelas V Di SD Inpres Mangempang Kabupaten Gowa - Wardiana Said, Sri; Damopolii, Muljono; Rasyid, Muh Rusydi (JURNAL KAJIAN ISLAM MODERN, 2024)
The aim of this research is to: 1) Find out the reality of students' conceptual and factual knowledge in class V science learning at SD Inpres Mangempang, Gowa Regency before implementing the experiential learning model, 2) Find out the reality of students' conceptual and factual knowledge in class V science learning at SD Inpres Mangempang Gowa District after implementing the experiential learning model, 3) Find out whether there is an influence on students' conceptual and factual knowledge through the application of the Experiential Learning model in class V science learning at SD Inpres Mangempang, Gowa District. The design of this research is a pre-experimental one group pretest posttest design. The total population is all 19 class V students at SD Inpres Mangempang. The data collection technique used was a test (pretest posttest). Data analysis techniques use descriptive analysis and difference analysis. Based on the results of descriptive analysis, it shows that the average reality value of students' conceptual and factual knowledge before implementing the experiential learning model is 29.47 Meanwhile, the average reality value of students' conceptual and factual knowledge after implementing the experiential learning model was 87.37. The results of the difference analysis using the Paired Sample t-Test can be said to be influential if the value of the sig (2-tailed) is smaller than 0.05. After carrying out the paired sample t-Test, a value of 0.000 is obtained. It can be concluded that there is a significant influence on students' conceptual and factual knowledge before and after being given treatment using the experiential learning model. The implications of this research are: For teachers, the learning process using the experiential learning model can be chosen as a learning model that can be applied to increase students' conceptual and factual knowledge. For students, implementing the experiential learning model can help increase student involvement in learning. For researchers, the results of this research can be used as a reference for future researchers